Social media’s influence and service quality on purchasing decisions: a study of PT. Toyota Astra Finance - Irdha Yusra; Rada Sri Rahayu (Marketing Management Studies, 2022)
This study aims to determine the effect of social media promotion as a marketing Strategy and service quality to improve purchasing decisions for financing servises products in PT. Toyota Astra Finance branch padang. The sampling method used a purposive sampling technique of 70 samples. The data analysis used was the research instrumenttest, classical assumption test, multiple linear regression analysis, and hypothesis testing. The results of this study show that social media promotion has a positive and significant effect on buyer decisions, service quality does not significantly affect purchasing decisions and simultaneously there is a significant influence on social media promotion and service quality on purchasing decisions